ANALISIS PENGARUH SUKU BUNGA TERHADAP KINERJA KEUANGAN DAN KINERJA SAHAM PERBANKAN DI INDONESIA - Mokhammad Fadhil Adnanhasan; Noer Azam Achsani; Tanti Novianti (Jurnal Proaksi, 2020)
The interest rate change policy is also considered by investors to influence the banking performance of financial performance and changes in stock prices. The policy of determining the benchmark interest rate is considered to be an important thing that can affect the banking sector, both in terms of financial performance and stock performance. This research was conducted in all three Banks Book and four Banks Book listed on the IDX by analyzing the Bank's annual financial statements as well as the trend of the movement of the company's stock performance from 2010 to 2018. Bank financial performance is an important factor that needs to be considered to improve stock performance . This is due to the processing results showing a significant influence besides the interest rate policy known to have a significant effect on the performance of bank shares. Keywords: Interest Rate, Banking Performance, Stock